Online identification of adsorption isotherms in SMB processes via efficient moving horizon state and parameter estimation - Küpper, Achim; Wirsching, Leonard; Diehl, Moritz; Schlöder, Johannes P.; Bock, Hans Georg; Engell, Sebastian (Computers & chemical engineering, 2010)
In this paper, a concept to identify the adsorption isotherm of Simulated Moving Bed processes online during the operation is proposed. The influence of model parameters on the measurements is analyzed by a sensitivity analysis which enables to identify the set of parameters that can be estimated simultaneously. The parameters are estimated in real-time by a moving horizon state and parameter estimation scheme. Numerical simulations of validated models for separation problems with nonlinear isotherms of Langmuir type are presented. Furthermore, it is it shown that a structural plant/model mismatch in the void fraction can be compensated to a large extent by modifying the Henry coefficients of the adsorption isotherm such that the estimated model can be used in the context of online optimizing control.
Gesehen am 08.03.2023